2018
DOI: 10.1063/1.5009184
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent N-polar (In,Ga)N/GaN quantum wells achieved by plasma-assisted molecular beam epitaxy at temperatures exceeding 700 °C

Abstract: N-polar (In,Ga)N/GaN quantum wells prepared on freestanding GaN substrates by plasma-assisted molecular beam epitaxy at conventional growth temperatures of about 650 • C do not exhibit any detectable luminescence even at 10 K. In the present work, we investigate (In,Ga)N/GaN quantum wells grown on Ga-and N-polar GaN substrates at a constant temperature of 730 • C. This exceptionally high temperature results in a vanishing In incorporation for the Ga-polar sample. In contrast, quantum wells with an In content o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Because of the high reactivity of Al with O, the doping level could very well be substantially higher than in GaN (see, e.g., ref 42 for studies of metal-polar films), but we are not aware of data for N-polar (Al,Ga)N. For GaN of either polarity, there is general agreement that O incorporation is reduced substantially with increasing growth temperature. 43,44 Our nanowires were grown at temperatures not accessible for planar layers (820 °C), and we would thus expect that O incorporation is reduced even further. For a quantitative estimate, we examined the APT data for the presence of O but also C, Ca, and B (which are the most abundant impurities in GaN layers grown by PAMBE).…”
Section: Nano Lettersmentioning
confidence: 99%
“…Because of the high reactivity of Al with O, the doping level could very well be substantially higher than in GaN (see, e.g., ref 42 for studies of metal-polar films), but we are not aware of data for N-polar (Al,Ga)N. For GaN of either polarity, there is general agreement that O incorporation is reduced substantially with increasing growth temperature. 43,44 Our nanowires were grown at temperatures not accessible for planar layers (820 °C), and we would thus expect that O incorporation is reduced even further. For a quantitative estimate, we examined the APT data for the presence of O but also C, Ca, and B (which are the most abundant impurities in GaN layers grown by PAMBE).…”
Section: Nano Lettersmentioning
confidence: 99%
“…It is likely related to the difference in defect formation mechanics, e.g. higher layer contamination [5,6] for growths in the N-polar orientation by metalorganic vapor phase epitaxy (MOVPE) and by molecular beam epitaxy (MBE) [4,[7][8][9][10], due to the drastically different growth dynamics and chemistry of the N-polar and Ga-polar structures. If the reason for the low IQE of N-polar quantum wells is discovered and solved, and the IQE is brought up to the level of Ga-polar heterostructures, constructing LEDs (or laser diodes) requires placing the quantum wells inside the depletion region of a p-n junction diode.…”
Section: Introductionmentioning
confidence: 99%
“…We recall that these layers were grown at about 700 and 715 ℃, respectively. Chèze et al [23] have also reported a slightly larger Ca concentration of 3 -5 × 10 17 cm −3 for a N-polar GaN buffer grown by PA-MBE at 730 ℃ whereas Young et al [24] found only 8×10 15 cm −3 of Ca impurties in a Ga-polar GaN buffer grown by NH 3 -MBE at 820 ℃. Hence, in addition to the growth temperature [24], the Ca incorporation rate appears to be drastically affected by the MBE growth method and the crystal orientation.…”
Section: B Impurity Concentrationmentioning
confidence: 97%
“…The origin of this phenomenon is related to the presence of nonradiative defects at the QW/barrier interface. A potential candidate for this as yet unknown point defect is * Electronic mail: auzelle@pdi-berlin.de the impurity Ca [22,23] which can contaminate the substrate surface during wet cleaning and gradually incorporates in the overgrown nitride layers [24].…”
Section: Introductionmentioning
confidence: 99%